2017
DOI: 10.1002/smll.201701921
|View full text |Cite|
|
Sign up to set email alerts
|

Drug Delivery to the Brain across the Blood–Brain Barrier Using Nanomaterials

Abstract: A major obstacle facing brain diseases such as Alzheimer's disease, multiple sclerosis, brain tumors, and strokes is the blood-brain barrier (BBB). The BBB prevents the passage of certain molecules and pathogens from the circulatory system into the brain. Therefore, it is nearly impossible for therapeutic drugs to target the diseased cells without the assistance of carriers. Nanotechnology is an area of growing public interest; nanocarriers, such as polymer-based, lipid-based, and inorganic-based nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
136
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(140 citation statements)
references
References 161 publications
(167 reference statements)
0
136
0
4
Order By: Relevance
“…The resonance multiplicity in the 1 H NMR spectra are described as “s” (singlet), “d” (doublet), “t” (triplet), and “m” (multiplet) and broad resonances are indicated by “b”. Residual protic solvent of CDCl 3 ( 1 H, δ 7.27 ppm; C, δ 77.0 ppm (central resonance of the triplet)), DMSO‐ d 6 ( 1 H, δ 2.50 ppm), and MeOD ( 1 H, δ 3.31 ppm and C, δ 49.0 ppm) were used for chemical shifts calibration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resonance multiplicity in the 1 H NMR spectra are described as “s” (singlet), “d” (doublet), “t” (triplet), and “m” (multiplet) and broad resonances are indicated by “b”. Residual protic solvent of CDCl 3 ( 1 H, δ 7.27 ppm; C, δ 77.0 ppm (central resonance of the triplet)), DMSO‐ d 6 ( 1 H, δ 2.50 ppm), and MeOD ( 1 H, δ 3.31 ppm and C, δ 49.0 ppm) were used for chemical shifts calibration.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the field of drug delivery has been revolutionized with a plethora of innovative nanotechnology‐based products which can effectively diffuse through the biological barricades within the body and deliver payloads of drugs, DNA, proteins or peptides to injured or diseased cells and tissues . Despite the significant growth in the field of nanotechnology, nanoparticles face challenges during clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] It is reported that nearly 98% of small‐molecule drugs or contrast agents and most macromolecular drugs are routinely excluded from the brain, which makes the treatment and imaging of brain tumors extremely difficult. [ 5,6 ] Although the tight junctions of BBB at the late stage of brain tumors are disrupted to permit drug penetration into brain, the drug concentration in tumor sites is not sufficient to reach the therapeutic level. [ 7 ] More importantly, the treatment of the early stage of brain tumors is more challenging due to the presence of almost intact BBB.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6,9 ] Nanoparticles conjugating a positively charged moiety, such as a cell penetrating peptide (CPP), can contact with the membrane surface of BBB (with negative charge) to traverse the BBB by AMT. [ 5,10 ] But the ability of such nanoparticles to traverse the BBB is relatively low because of limited affinity, lack of selectivity, and easy immune clearance. RMT is the most commonly adopted strategy, which involves the binding of target ligands conjugated onto the nanoparticle to corresponding receptors expressed on the surface of brain endothelial cells to improve the delivery of loaded therapeutic agents into the brain.…”
Section: Introductionmentioning
confidence: 99%
“…[ ][ ] One approach to reduce such side effects is through the use of nanosized drug delivery systems (DDS). Classic DDS are either composed of inorganic materials or made from self‐assembled soft matter . The latter are typically composed of amphiphilic molecules that can be loaded with various molecules of therapeutic interest .…”
Section: Introductionmentioning
confidence: 99%